Republic of North Macedonia : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for the Republic of North Macedonia. (IMF Staff Country Reports; Country Report, 2020)
This paper highlights the Republic of North Macedonia's Request for Purchase Under the Rapid Financing Instrument (RFI). North Macedonia's economic outlook has deteriorated substantially due to the coronavirus disease 2019 (COVID-19) pandemic. Real GDP is expected to decline by 4 percent in 2020 due to a fall in both domestic and external demand. This, together with negative shocks to confidence and spill-overs from global financial channels, has created an urgent balance of payments need. The authorities quickly responded with targeted and temporary fiscal policy support to limit the social and economic impact of the health emergency by protecting the liquidity of companies, preserving jobs and providing social care for the jobless and vulnerable households. The authorities have also expressed their strong commitment, once the COVID-19 crisis is over, to rebuilding fiscal buffers and implementing the structural reform agenda to help preserve debt sustainability and speed up income convergence to European Union countries.